The Difference Scientific Literacy ability of Student having Field Independent and Field Dependent Cognitive style - Rahmania, Septi; Miarsyah, Mieke; Sartono, Nurmasari (Universitas Negeri Jakarta, 2015)
Scientific Literacy refers to an individual scientific knowledge and use it to identifiy question, aquire new knowledge, explain scientific phenomena, and draw evidence based conclusion about science related issues. Scientific literacy is the final purpose of learning science for 15 years students. In learning process, students have different modal to achieve the science learning purpose. One of modal that student have named cognitive style. Different cognitive style assumed to be different scientific literacy ability. Cognitive style in this research is according to Witkin and Goodenough (1981) in Altun and Cakan (2006) i.e Field Independent (FI) and Field Dependent (FD). Purpose of this research is to know the difference scientific literacy ability of students having Field Independent and Field Dependent cognitive style. This research was conducted at SMAN 68 Jakarta in April until Mei 2015. Method use in this research was Ex Post Facto. The sample were 135 X grade High School Students ( 21 FD and 114 FI). The result of prerequisite test use Kolmogorov-smirnov (Î± = 0,05) and Levene test (Î± = 0,05) showed the data normally distributed and homogenous. Result of Independent t-test (Î± = 0,05) showed p value 0,002<0,05 thereby there is the differences between FI and FD on scientific literacy score and level. Students with FI cognitive style obtain higher score than students with FD cognitive style with mean difference 9,849.